Group Guidance to Increase Peer Counselor and Understanding of Bullying - Yuliana Yuliana; Neviyarni Neviyarni; Marlina Marlina (International Journal of Applied Counseling and Social Sciences, 2020)
Peer counsellors have a low understanding of bullying and assume that bullying is common. The purpose of this research is to determine the effectiveness group counselling services to increase peer counsellor understanding of bullying. Methods Quasi Experiment study approach through the design of The Non-Equivalent Control Group. Data were collected using a peer counsellor understanding scale about bullying (53 valid items = 0.949). The study sample consisted of 10 peer counsellors as a control group and 10 peer counsellors as an experimental group who had a low and moderate understanding. Data were analyzed using the Wilcoxon Signed-Rank test and Kolmogorov-Smirnov two independent sample. The findings of this study showed that group counselling services are effective in improving the understanding of peer counsellor about bullying.